Optimized bio-photonic sensor using 1D-photonic crystals as a blood hemoglobin sensor. (29th December 2020) - Abd El-Ghany, S E-S; Noum, Walaa M; Matar, Z S; Zaky, Zaky A; Aly, Arafa H
Abstract: In this paper, a blood hemoglobin sensor is designed and analyzed by using a defected one-dimensional photonic crystal (1DPhCs). A structure of a binary defected 1D-PC is proposed. The structure is optimized by considering the effect of the angle of incidence, the defect layer thickness, and the refractive index of the first layer. The average sensitivity of the optimized sensor (Si/SiO2 ) N /Dd /(Si/SiO2 ) N is about 1025 nm/RIU. We have used the transfer matrix method in our study by using the MATLAB code to achieve the present results.